2022
DOI: 10.1186/s13068-022-02204-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C/N ratio on the growth and protein accumulation of heterotrophic Chlorella in broken rice hydrolysate

Abstract: Background Microalgae protein is considered as a sustainable alternative to animal protein in the future. Using waste for microalgal culture can upgrade low-value raw materials into high-value products, helping to offset the cost of microalgal protein production. In this study we explored the feasibility of using microalgae heterotrophic fermentation to convert broken rice hydrolysate (BRH) into protein. Results The results showed that the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
4
7
0
Order By: Relevance
“…match with those in the literature, yet the overall content does not [ 20 ]. A culture medium with a carbon to nitrogen ratio tending towards nitrogen promotes the production of amino acids [ 21 ]. We assume that a nitrogen-poorer cultivation is causing the lower amino acid concentrations in the analyzed microalgae compared to the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…match with those in the literature, yet the overall content does not [ 20 ]. A culture medium with a carbon to nitrogen ratio tending towards nitrogen promotes the production of amino acids [ 21 ]. We assume that a nitrogen-poorer cultivation is causing the lower amino acid concentrations in the analyzed microalgae compared to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae in the growth phase were shown to accumulate more amino acids with two or more nitrogen atoms, such as histidine and arginine but also ornithine. This might be due to a greater availability of nitrogen in the culture medium, since microalgae cultivated in a nitrogen-rich medium synthesize amino acids rich in nitrogen [ 21 ]. Furthermore, the additional increase in the non-protein amino acid ornithine is plausible, due to its role as a precursor for arginine synthesis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these results were somehow expected since FW 5 and 6 have fish in their composition. Regarding the impact of C:N ratios, Cai et al [27] demonstrated the effect of different ratios on the growth and protein accumulation of C. vulgaris grown under heterotrophic culture conditions using rice hydrolysate. This study showed that nitrogen became a limiting factor for microalgal growth when the C:N ratios exceeded 19:1, resulting in lower biomass productivity.…”
Section: Chemical Characterization Of the Food Wastesmentioning
confidence: 99%
“…In general, all the FW formulations had higher ratios than the Redfield ratio, but the value associated with this one (37.22) may have resulted in a more unbalanced supplementation, leading to growth inhibition. For example, the study conducted by Cai et al [27] focused on the influence of different C:N ratios, ranging from 5:1 to 48:1, on the heterotrophic growth of C. vulgaris. It was observed that, at higher ratios, besides inhibiting growth, not all the reducing sugars present in the culture medium were consumed.…”
Section: Heterotrophic Growth Of C Vulgarismentioning
confidence: 99%